Development of sprouted green gram and gram flour biscuits and evaluation of sensory attributes - Gupta, Sonam; Bhatt , Devender Kumar (Journal of Postharvest Technology, 2023)
This study investigated the impact of incorporating sprouted gram and mung flour on the sensory attributes of biscuits. The sprouted flours were prepared by sprouting raw gram and mung beans, drying them in a cabinet dryer, and grinding them into flour. The biscuit dough was then prepared by mixing the flours with sugar, butter, baking powder, baking soda, and water. The dough was rolled, cut into shapes, and baked at a specific temperature for a set time. Sensory evaluations were conducted by a panel using a 9-point hedonic scale to assess taste, shape, texture, color, crunchiness, and overall acceptability. The results showed that biscuits containing sprouted gram and mung flour received higher scores for color, crunchiness, and overall acceptability compared to the control. Therefore, the addition of sprouted gram and mung flour can be a promising ingredient for producing biscuits with improved sensory quality.